PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE ARCHERIES TANGERANG SELATAN - Rani Silviya Sari; Ade Yusuf (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of price and service quality on consumer satisfaction at Archeries Cafe, South Tangerang. The research method used is descriptive quantitative, with the population in this research being all consumers of Cafe Archeries, South Tangerang, namely 15,569 consumers. The sampling technique used a simple random sample using the Slovin formula, obtaining 100 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are multiple regression, namely that price and service quality have a significant effect on consumer satisfaction with the regression equation Y = 6.672+ 0.532 hypothesis testing obtained tcount > ttable or (5.519 > 1.984). Price has a significant effect on consumer satisfaction. Hypothesis testing of service quality on consumer satisfaction obtained t count > t table or (2,830 > 1.984). Meanwhile, for the hypothesis test, the calculated F value > F table or (15.110 > 3.09) was obtained, thus H0 was rejected and H3 was accepted, meaning that there was a simultaneous positive and significant influence between price and service quality on consumer satisfaction at the Archeries Cafe, South Tangerang